(untitled) (Philological Studies, 2019)
Andrić’s Bosnia is the area that the author portraits in its variety of life and distinctive situations occurring in the private and public sphere: as the protagonists act people from different social classes, nationalities and denominations. Therefore, great narrative work of Ivo Andrić offers the possibility of classification and selection according to the different criteria. The paper shall analyze some of the thematic and stylistic aspects in The Friar’s Stories (ten Andrić’s short stories written in the period from 1923 to 1951 with the Bosnian friars acting as the main protagonists).